Social Determinants of Health in Rural and Urban Communities - GC, Krishna Bahadur (Prāgyik Prabāha, 2023)
The purpose of this study is to better understand the social factors that influence the health of community members. Both a descriptive and a narrative study design were used to create this article. The social determinants of health (SDH), which are non-medical factors that can be changed by social policies and have a major impact on health, have attracted the attention of the public health community during the past two decades. SDH are non-medical factors that can be changed by social policies and substantially impact health. It is clear that there is widespread support for an SDH approach around the world, ranging from national action to global political commitment. The purpose of this study is to explore the social factors that influence the health of community members. However, differences in the conditions in which people are born, raised, employed, and aged result from differences in power, wealth, and resources. Political, economic, and resource allocation decisions made outside the health sector must consider health as a result throughout the social distribution in order to prevent a concentration primarily on increasing production. Health can be considered in any plan, which can help to some extent to ensure that it is considered. By tracking the development of SDH on a global basis and concentrating on how successful policies and implementation plans may be enhanced going forward, standard procedures will be discovered and exchanged. The WHO's attempts to align measures with the SDGs will boost the assessment of progress.